Photosensitive electrocatalysts based on Ni–WS2 nanohybrids for hydrogen evolution reaction. (14th October 2021) - Pataniya, Pratik M; Patel, Meswa; Srivastava, Divesh N; Sumesh, C K
Abstract: Efficient hydrogen evolution by electrolysis plays an indispensable role for hydrogen fuel generation in green energy devices. In order to implement high-performance electrocatalytic activity, it is usually necessary to design economically viable, effective and stable electrocatalysts to reduce activation potential barriers. Herein, we report the photosensitive Ni–WS2 nanohybrids for enhanced electrocatalytic hydrogen evolution reaction (HER). Optimisation of chemical composition in catalysts has resulted in the rapid water electrolysis which was further promoted by illumination of 532 nm light. Obvious HER has been achieved at over potential of as low as −210 mV versus RHE without and −190 mV versus RHE (at −10 mA cm −2 ) with illumination. Being a photosensitive electrocatalysts, Ni–WS2 Nanohybrids have demonstrated stable time-resolved photoresponse with photocurrent of 12.7 mA cm −2 at −250 mV V versus RHE as well as self-powered photodetection with current 0.68 mA cm −2 . Finally, HER with improvement under visible light illumination has shown considerable development in clean energy generation by using renewable energy sources.